Penyelesaian Sengketa Antara Bank dan Nasabah Oleh Lembaga Mediasi Perbankan - Meita Djohan Oelangan (Universitas Bandar Lampung (UBL), 2010)
The protection and empowerment of customers is the infrastructure existence of thebank to handle and complaints resolving and customer complaints. There is now, analternative dispute resolution through mediation between banks and customers. Article8 of Bank Indonesia Regulation (PBI) No. 8/5/PBI/2006, the dispute to be submittedin writing accompanied by supporting documents according to formats. The disputewas not raised in the process or have not been decided by arbitration institution orjudicial institutions. Disputes filed a civil disputes: the mediation process is conductedafter the customer and bank to signed the Mediation Agreement, that includes anagreement choosing mediation as alternative dispute resolution and agreement toabide by the rules of mediation are set by Bank Indonesia, then the bank shall followthe Mediation Agreement, which was signed by customer or lawyer and bank.